2019
DOI: 10.29262/ram.v66i3.401
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab as an adjuvant therapy for treating severe atopic dermatitis in children. A series of cases

Abstract: Antecedentes: La dermatitis atópica (EA) es una enfermedad crónica de la piel que afecta de 5 a 20% de los niños. Esta enfermedad compromete la calidad de vida. El omalizumab ofrece un papel prometedor en el tratamiento de la dermatitis atópica severa. Objetivo: Dar a conocer nuestra experiencia con el uso de omalizumab para la dermatitis atópica severa en niños.Métodos: Revisión retrospectiva de los casos de pacientes pediátricos con dermatitis atópica severa tratados con omalizumab como terapia adyuvante en … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…44 , 50 Garcia et al reported a series of evaluation in 19 patients and reported 85.7% patients moved from severe to mild or moderate disease severity at the end of treatment. 52 Among 14 AD patients comorbid with asthma, 12 showed significant reduction in severity of both asthma and AD after q2w omalizumab therapy for 1 year. 49 Belloni et al reported data from 11 AD patients treated with omalizumab for 20 weeks, showed good clinical response in 6 patients.…”
Section: Anti-ige Therapy In Atopic Dermatitismentioning
confidence: 98%
See 1 more Smart Citation
“…44 , 50 Garcia et al reported a series of evaluation in 19 patients and reported 85.7% patients moved from severe to mild or moderate disease severity at the end of treatment. 52 Among 14 AD patients comorbid with asthma, 12 showed significant reduction in severity of both asthma and AD after q2w omalizumab therapy for 1 year. 49 Belloni et al reported data from 11 AD patients treated with omalizumab for 20 weeks, showed good clinical response in 6 patients.…”
Section: Anti-ige Therapy In Atopic Dermatitismentioning
confidence: 98%
“…The use of omalizumab in patients with AD has been presented in multiple case series and case reports. 42 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 Details on these cases are summarised in Table 1 . Patients across regions with average age ranging between 7 and 51 years, extremely variable levels of baseline IgE, and omalizumab (150–600 mg q2w or q4w) treatment duration between 8 and 292 weeks, have been studied.…”
Section: Anti-ige Therapy In Atopic Dermatitismentioning
confidence: 99%
“…Efficacy and safety of Omalizumab in treatment of IgE‐mediated conditions like allergic asthma and rhinitis has been demonstrated, 9 some studies define this therapy as an effective and useful concomitant therapy in pediatric refractory severe AD, 10,11 especially improving the quality of life, reducing the severity of skin lesions and the need for systemic therapies (steroids, immunosuppressors) with their potential side‐effects.…”
Section: Discussionmentioning
confidence: 99%
“…8 Efficacy and safety of Omalizumab in treatment of IgE-mediated conditions like allergic asthma and rhinitis has been demonstrated, 9 some F I G U R E 3 A-D, Significant improvement of lower limbs before, A and B, and after, C, therapy with persistence of lichenification but complete disappearance of exudation F I G U R E 2 A-D, Atopic eczema of the upper trunk before, A and C, and after, B and D, 3 months of therapy with Omalizumab. Reduction of active lesions and scratching signs with the prevalence of postinflammatory hyperpigmentation can be noted studies define this therapy as an effective and useful concomitant therapy in pediatric refractory severe AD, 10,11 especially improving the quality of life, reducing the severity of skin lesions and the need for systemic therapies (steroids, immunosuppressors) with their potential side-effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation